Comparison of physical performance between older adult fallers with and without knee osteoarthritis - Pavapriya Ponvel,; Devinder Kaur Ajit Singh,; Soon Ming Shan,; Siti Salwana Kamsan,; Mohd Azzuan Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Knee osteoarthritis (OA) is a common musculoskeletal condition that leads to decreased physical performance and falls among older adults. However, there is limited information comparing physical performances among older adult fallers with and without knee OA. The aim of this study was to compare physical performance between older adult fallers with and without knee OA. Participants were divided into two groups using the clinical diagnosis of knee OA based on National Institute of Health and Care Excellence guidelines; with and without knee OA. Participants performed a battery of physical performance tests that included chair sit and reach, back scratch, dominant handgrip strength, timed up and go (TUG), 30 seconds chair stand and 2 min walk. Independent t-test was used to compare physical performance between groups. Thirteen older adult fallers with knee OA (mean age = 70.92 ± 8.83 years) and 20 older adult fallers without knee OA (76.4 ± 7.92 years) participated in this study. There were no significant differences in sociodemographic profiles and physical performance among older adult fallers with and without knee OA (p > 0.05). However, hamstring flexibility was not within norm in 64% of older adult fallers with knee OA compared to 42% without OA. Physical performance between fallers with and without clinically diagnosed knee OA was similar. Hence, physiotherapy interventions for both groups may be similar and focused on strength and endurance training. In addition, to minimize falls risk and further improve physical performance, hamstring stretching must be emphasized among older adults with knee OA.